2019
DOI: 10.1111/jspn.12263
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maintaining web‐based diaries by caregivers on adherence to care regimens in preschoolers with asthma

Abstract: Background The objective of this pilot study was to assess the effects of maintaining web‐based diaries by the caregivers of preschoolers with asthma on the adherence to asthma care regimens, the recognition of asthma symptoms, and their perceived levels of parenting stress, quality of life, and family functioning. Design and Methods The caregivers of preschoolers with asthma completed a 4‐week web‐based diary and received weekly emails that depicted their children's asthma symptoms. We compared asthma symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Most studies (19/23, 83%) showed a positive effect of their digital intervention on controller medication adherence [96,98,304,305], whereas few studies showed no effect [208,297]. This corresponds with the review results of Ramsey et al [8], who showed that 87% of digital interventions improved adherence.…”
Section: Adherencesupporting
confidence: 70%
See 1 more Smart Citation
“…Most studies (19/23, 83%) showed a positive effect of their digital intervention on controller medication adherence [96,98,304,305], whereas few studies showed no effect [208,297]. This corresponds with the review results of Ramsey et al [8], who showed that 87% of digital interventions improved adherence.…”
Section: Adherencesupporting
confidence: 70%
“…Of the 19 studies that reported on the effect regarding QoL, 10 reported a positive effect [8,98,290,303] and the other 9 reported no difference [14,293,304,305] regarding the studied intervention. There was no clear difference in the types of interventions that had significant or no significant effect on QoL.…”
Section: Qolmentioning
confidence: 99%
“…Of the 19 studies that reported on the effect regarding QoL, 10 reported a positive effect [ 8 , 98 , 290 , 303 ] and the other 9 reported no difference [ 14 , 293 , 304 , 305 ] regarding the studied intervention. There was no clear difference in the types of interventions that had significant or no significant effect on QoL.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies (19/23, 83%) showed a positive effect of their digital intervention on controller medication adherence [ 96 , 98 , 304 , 305 ], whereas few studies showed no effect [ 208 , 297 ]. This corresponds with the review results of Ramsey et al [ 8 ], who showed that 87% of digital interventions improved adherence.…”
Section: Resultsmentioning
confidence: 99%